Effects of combined strength and kick coordination training on soccer kick biomechanics in amateur players - Manolopoulos, E.; Papadopoulos, C.; Kellis, E. R. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The aim of this study was to examine the effect of a soccer (strength and technique) training program on kinematics and electromyographic (EMG) muscle activity during a instep kick. Ten amateur soccer players (aged 19.9±0.4 years, body mass 74.8±9.1 kg, height 177.4±6.7 cm) constituted the experimental group (EG) whereas 10 players (age 21.6±1.3 years, weight 71.5±6.7 kg, height 175.2±3.4 cm) served as controls (CG). The EG followed a 10-week soccer-specific training program combining strength and technique exercises. All participants performed an instep soccer kick using a two-step approach while three-dimensional data and EMG from six muscles of swinging and support legs were recorded prior to and after training. Maximum isometric leg press strength, 10-m sprint performance and maximum speed performance on a bicycle ergometer were also measured. Analysis of variance designs with repeated measures showed that the EG improved significantly (P<0.05) maximum ball speed, the linear velocity of the foot, ankle and angular velocity of all joints during the final phase of the kick. Training had insignificant effects on EMG values, apart from an increase in the averaged EMG of the vastus medialis whereas maximum isometric strength and sprint times significantly improved after training (P<0.05). The present results suggest that the application of the training programs using soccer-specific strength exercises would be particularly effective in improving of soccer kick performance.